Green synthesis of silver nanoparticles from papaya seed extracts with alkaloid content for antibacterial application - Hedya Nadhrati Surura; Hairus Abdullah; Sahna Ferdinand Ginting; Erny Tandanu; Refi Ikhtiari (Jurnal Teknologi Laboratorium, 2021)
This research aims to develop a silver nanoparticle (AgNPs) using several plant extracts for antibacterial application. The papaya seed extract has been fractioned by n-hexane, ethyl acetate, water, and ethanol. The n-hexane fraction was the only fraction that succeeded in synthesizing AgNPs. The characterization methods showed AgNPs marked at 430 nm with UV-Vis and 1640 cm-1 with FTIR. SEM observed the aggregation of spherical AgNPs at the 200 nm scale. The particle size of 91.3 nm was measured with PSA that confirmed the nanoscale of the synthesized material. All fractions contained alkaloid compound, and ethyl acetate fraction showed a group of indole with specific wavenumber at 2623 cm-1, 1737 cm-1, and 1237 cm-1 representing N-H, C=O, C-N, respectively. All fractions at every concentration (25%, 50%, 75%, 100%)  have been tested and showed the medium effect on bacterial growth inhibition. Among all fractions, the AgNPs n-hexane fraction has the highest bacterial effect, which was indicated by mean values of inhibition zone 7.2 mm against S.aureus, as well as 6.6 mm against E.coli. ANOVA analysis showed that AgNPs n-hexane fraction has a significant inhibition zone compared to other fractions against S.aureus (p=0.002), but not significant to E.coli (p=0.128). The insignificant results on E.coli because of gram-negative bacteria's biophysical characteristics, such as membrane cell wall and flagellin. This research emphasized that AgNPs could be synthesized via a green process of nucleation by using plant extract that effectively inhibits the growth of S.aureus and E.coli. Further studies on the mechanism of the antibacterial effect at the molecular level might be investigated soon.